Industrialisation and society : a social history, 1830-1951 - Hopkins, Eric (Routledge, 2000)
An essential introduction to the effects of industrialisation on British society, from Queen Victoria's reign to the birth of the Welfare State in the 1940s. It includes sections on the Victorian inheritance and the two world wars.
Keywords: Industrialization -- Social aspects -- Great Britain -- History.; Great Britain -- Economic conditions -- 19th century.; Great Britain -- Economic conditions -- 20th century.; Great Britain -- Social conditions -- 19th century.; Great Britain -- Social conditions -- 20th century.; Industries -- Social aspects -- Great Britain -- History.; Industrialisation -- Aspect social -- Grande-Bretagne -- Histoire.; Grande-Bretagne -- Conditions économiques -- 19e siècle.; Grande-Bretagne -- Conditions économiques -- 20e siècle.; Grande-Bretagne -- Conditions sociales -- 19e siècle.; Grande-Bretagne -- Conditions sociales -- 20e siècle.; SOCIAL SCIENCE -- Anthropology -- Cultural.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Popular Culture.; Economic history; Industrialization -- Social aspects; Industries -- Social aspects; Social conditions; Great Britain; Industrialisierung; Großbritannien; Industrialisatie.; Sociale geschiedenis.; 1800-1999; History